2009
DOI: 10.1007/s00262-009-0740-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic dysregulation of CEACAM1 in melanoma patients

Abstract: It was previously shown that CEACAM1 on melanoma cells strongly predicts poor outcome. Here, we show a statistically significant increase of serum CEACAM1 in 64 active melanoma patients, as compared to 48 patients with no evidence of disease and 37 healthy donors. Among active patients, higher serum CEACAM1 correlated with LDH values and with decreased survival. Multivariate analysis with neutralization of LDH showed that increased serum CEACAM1 carries a hazard ratio of 2.40. In vitro, soluble CEACAM1 was der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
76
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 39 publications
7
76
0
Order By: Relevance
“…This was in line with our findings that CEACAM1 protects melanoma cells and inhibits both activated NK cells (17) and activated T cells (19,20,24). Furthermore, we have recently shown an unusually high percentage of CEACAM1 þ circulating lymphocytes in the peripheral blood of patients with melanoma, as compared with healthy donors (24).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was in line with our findings that CEACAM1 protects melanoma cells and inhibits both activated NK cells (17) and activated T cells (19,20,24). Furthermore, we have recently shown an unusually high percentage of CEACAM1 þ circulating lymphocytes in the peripheral blood of patients with melanoma, as compared with healthy donors (24).…”
Section: Introductionsupporting
confidence: 91%
“…It has a strong prognostic value (23) implying on its clinical mechanistic importance. Mechanistically, CEACAM1 protects melanoma cells by inhibiting effector functions of NK cells (13,17,24) and T cells (19,20) in a homophilic manner. Indeed, blocking of CEACAM1 homophilic interactions with polyclonal antibodies enhanced the killing of CEACAM1 þ melanoma cells by NK and T cells (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it is known that CEACAM1 is a negative-regulator of cell proliferation and is down-regulated in some tumor cells (4 -10). Yet, CEACAM1 expression is reported to protect tumor cells from killing by immune cells (11)(12)(13)(14) and it has been found that the high expression level is associated with a number of other cancers (15)(16)(17)(18)(19). It is likely that this complex set of effects arises as a result of the numerous homophilic and heterophilic interactions that CEACAM1 can have with itself and other members of the CEACAM superfamily.…”
mentioning
confidence: 99%
“…In line with this idea, Markel and colleagues presented data that melanoma patient-derived NK cells show an irregular phenotype and lower levels of NKp46, NKp30, and CD16 while the expression NKG2D was not altered (31). Furthermore, they showed that NK cells from healthy donors behaved differently than patient-derived NK cells.…”
Section: Discussionmentioning
confidence: 92%
“…In 2002, Thies and colleagues showed that the CEACAM1 protein expression in primary cutaneous melanoma predicts the development of metastatic disease (30). Furthermore, levels of soluble CEACAM1 in sera from melanoma patients have been shown to inversely correlate with overall survival (31,32). This spurred discussion of CEACAM1 as a more specific and sensitive biomarker than those currently used, including melan-A, S100b, and HMB45, and has implicated CEACAM1 as a potential novel therapeutic target (14).…”
Section: Introductionmentioning
confidence: 99%